PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 21 PEKANBARU - Ennita Ennita '; Hendri Marhadi Hendri Marhadi; Otang Kurniaman Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low learning outcomes IPS students. This research aims to improve learning outcomes by implementing IPS cooperative learning model Numbered Heads Together (NHT) third grade students of SD Negeri 21 Pekanbaru. This research was conducted in the first semester of the year 2014/2015 in class III SD Negeri 21 Pekanbaru. This research is a classroom action research (PTK). The subjects were students of class III SD Negeri 21 Pekanbaru. The number of students as many as 36 people, consisting of 16 male students and 20 female students. Results of the study are known from before the implementation of cooperative learning model NHT, the average value of student learning outcomes is 64.2. After the implementation of cooperative learning model NHT or in the first cycle, gained an average of 68.3 learning outcomes, increased to 73.1 in the second cycle and the third cycle increased to 79.2. As for the activities of teachers and students increased by a percentage in the first cycle is 56.3% in the first meeting and 68.8% in the second meeting. In the second cycle with the percentage of 75.0% in the first meeting and the second meeting amounted to 81.3%. At the first meeting of the third cycle of 87.5% and 93.8% in the second meeting. Thus, the hypothesis which says if implemented model of cooperative learning Numbered Heads Together (NHT) is implemented, it can improve learning outcomes for Social Sciences (IPS) Elementary School third grade students 21 Pekanbaru, unacceptable.Keywords: Cooperative Learning Model NHT , Learning Outcomes .